Thoracoscopic resection of primary mediastinal liposarcoma: a case report and literature review - Yanhui Yang; Ji Li; Sipeng Cheng; Jinyuan Mei; Xin Cheng; Min Jing; Yi Wang (Journal of Cardiothoracic Surgery)
Abstract Background Primary mediastinal liposarcomas (PLMs) are extremely rare. Patients typically present with symptoms caused by tumor size, as the mass can compress surrounding tissues and organs. Here, we report a case of a large primary mediastinal liposarcoma that was successfully resected thoracoscopically. By reviewing the available literature on mediastinal liposarcomas and sharing perioperative insights, we aim to provide guidance on the diagnosis and surgical management of large mediastinal liposarcomas. Case presentation A 38-year-old male presented to our hospital with complaints of dysphagia after meals. Chest computed tomography (CT) revealed a large space-occupying lesion in the posterior upper mediastinum, and gastroscopy identified esophageal compression without evidence of new growth. The patient underwent thoracoscopic resection, resulting in significant improvement of his dysphagia postoperatively. He experienced no postoperative complications and was discharged one week following surgery. Conclusion The incidence of PLM is very low. Due to the proximity of vital structures such as the vena cava, esophagus, trachea, and subclavian artery, surgical resection presents elevated risks and complexity. While minimally invasive thoracoscopic techniques offer both safety and efficacy, careful preservation of surrounding organs is essential during the procedure.